2010
DOI: 10.1242/jeb.047225
|View full text |Cite
|
Sign up to set email alerts
|

Substrate diameter and compliance affect the gripping strategies and locomotor mode of climbing boa constrictors

Abstract: SUMMARYArboreal habitats pose unique challenges for locomotion as a result of their narrow cylindrical surfaces and discontinuities between branches. Decreased diameter of branches increases compliance, which can pose additional challenges, including effects on stability and energy damping. However, the combined effects of substrate diameter and compliance are poorly understood for any animal. We quantified performance, kinematics and substrate deformation while boa constrictors (Boa constrictor) climbed verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Similarly, the angle of the crossing region of both species of snakes in our study approached 90deg as cylinder diameter increased, and for a given diameter the value was greater for the boa constrictors than for the rat snakes (Figs1, 8). For boa constrictors climbing vertically, the decreased deformation of larger diameter ropes is correlated with increased crossing angles (Byrnes and Jayne, 2010). Thus, the decreased crossing angles of the rat snakes compared with the boa constrictors seem likely to impede their ability to form opposing grips or reflect the alternative strategy of applying normal forces on opposite sides of the surface at different locations along its length.…”
Section: Modes Of Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the angle of the crossing region of both species of snakes in our study approached 90deg as cylinder diameter increased, and for a given diameter the value was greater for the boa constrictors than for the rat snakes (Figs1, 8). For boa constrictors climbing vertically, the decreased deformation of larger diameter ropes is correlated with increased crossing angles (Byrnes and Jayne, 2010). Thus, the decreased crossing angles of the rat snakes compared with the boa constrictors seem likely to impede their ability to form opposing grips or reflect the alternative strategy of applying normal forces on opposite sides of the surface at different locations along its length.…”
Section: Modes Of Locomotionmentioning
confidence: 99%
“…For example, the lack of surface deformation when boa constrictors use concertina locomotion to climb thick ropes suggests they use opposing grips, whereas deformation of thinner ropes suggests these snakes press inward at different locations (Byrnes and Jayne, 2010). The preponderance of ventral contact on thicker cylinders also suggests an important role for muscles that flex the vertebrae ventrally, whereas the more extensive contract between the lateral surfaces of the snakes and the thin vertical cylinders suggests an increased importance of the lateral flexors for gripping (Byrnes and Jayne, 2010). If snakes use two distinct gripping strategies with both path-following and non-path-following kinematics (Fig.2) (Astley and Jayne, 2007;Byrnes and Jayne, 2010), then this may represent four distinct patterns of arboreal concertina locomotion from the combined data for only two species.…”
Section: Modes Of Locomotionmentioning
confidence: 99%
“…Previous investigators have not yet observed snakes climbing diagonally or helically. On pillars much thinner than a snake length, Jayne showed that snakes perform concertina motion by coiling; however, the motion of their center of mass is purely linear [14]. A modular snake-like robot by Choset forms a helix around a column, climbing by rolling its parts while maintaining its helical configuration [15].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the effects of environmental variation on performance can lead to insights into what factors limit performance in a variety of taxa and locomotor tasks (Altshuler and Dudley, 2003;Byrnes and Jayne, 2010;Channon et al, 2011;Daley and Biewener, 2003). Two common and important features of arboreal habitats are the gaps between solid surfaces and the highly variable threedimensional trajectories that may be required to move or reach from one location to another.…”
Section: Limits To Gap-bridging Performancementioning
confidence: 99%